Evaluation of the "meat" basic cashew(Anacardium occidentale L.) submitted to different cooking methods and sensory acceptance of new products. - NatÃlia Rocha Sucupira (2012)
The growing demand for processed food products means there is a need to develop technologies which can lead to products being developed which only slightly alter the sensory and nutritional characteristics and which are easy to use. Cooking a food leads to significant changes in its chemical composition which affect the concentration and the bioavailabilty of the bioactive compounds of vegetables. The development of value-added food products from the waste processing of the cashew apple could be attractive to the growing market for products with a reduced level of fats and attractive sensory characteristics. Considering the lack of data on the characteristics of products obtained from the cashew apple, the aim of this study was to analyze the bioactive compounds of different âin naturaâ cashew apple fibers (artisan and industrialized), to compare the different methods of cooking of the cashew meat to find the best one after the different methods of cooking, as well as to elaborate a way of evaluating the acceptance and sensorial preference of the new products made from these fibers. Different types of cashew âmeatâ were made from fibers (artisan and industrialized). These types of âmeatâ underwent different methods of cooking (boiling, steaming, frying and a mixed method) and their bioactive compounds were measured (that is, ascorbic acid, total carotenoids, total antioxidant activity through the ABTS method âazinobis (3-ethylbenzothiazoline 6-sulfonic acid) and the DPPH method (2.2-diphenyl-1-picrylhydrazyl). Cashew flour and cashew balls were made and underwent sensorial analysis. The level of ascorbic acid, the total carotenoids, and the antioxidant activity measured by the ABTS and the DPPH methods showed significant differences between the two in natura fibers studied, while they were significantly similar in terms of phenolic compounds. The artisan cashew fiber had a high level of ascorbic acid, (147.8 mg.100g-1), which is an excellent source of vitamin C. Both fibers showed low levels of total phenolic compounds and showed antioxidant activity. In both, the levels of ascorbic acid and carotenoids were high as the basic cashew âmeatâ is a good source of these bioactive compounds. The boiling method of cooking was the one which led to the lowest retention of functional compounds, exhibiting the lowest measurements in all the parameters evaluated. In general, frying and the cooking method combining both dry and moist heat had the highest measurements and were not significantly different from each other. The cashew flour and cashew balls were judged to be acceptable on the hedonic scales used both in terms of their attributes (appearance, aroma, taste, overall impression) and intention to buy. The values ranged from âI liked a littleâ and âI liked quite a lotâ for attributes and in terms of intention to buy the possibilities were âmaybe Iâd buy, maybe notâ and âI would possibly buyâ. It can be seen that making use of cashew apple residue is important both in terms of combating waste and in the development of new food products.